(untitled) (Editora Impacto Científico, 2025)
The continuous advancement of technologies has significantly transformed various sectors of society, particularly the educational field, demanding a restructuring of teaching and learning approaches. The presence of digital tools in the school environment represents not only a possibility but a necessity in light of new informational and communicational demands. Nevertheless, many educators still face challenges in adapting their practices, especially when it comes to integrating these resources into already established contexts. This research aims to present to education professionals the importance of teacher preparation with the integration of new technologies into the curriculum. The study was based on a bibliographic investigation, involving the collection and analysis of academic publications available on digital platforms, with a focus on Portuguese-language content. The main objective was to identify key obstacles encountered in everyday school life, such as lack of preparation, limited access to equipment, and the persistence of traditional teaching methods. The analysis shows that, to keep pace with ongoing social and cultural transformations, it is essential to rethink pedagogical practices and expand access to innovative experiences within the school space. The conscious and creative use of digital tools can enhance student engagement, stimulate critical thinking, and contribute to more meaningful learning. Future studies may further explore viable paths for this restructuring, taking into account local realities and collaborative possibilities across different areas of knowledge.